SOCIALIZATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES FOR STUDENTS OF SENIOR HIGH SCHOOL KRISTEN IRENE MANADO - Lonto, Miryam Pingkan; Tangkau, Jaqueline (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This Community Service activity aims to provide accounting knowledge and preparation of financial statements based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) to high school students. Irene Christian High School students are prospective S1 Accounting students and also business actors so it is necessary to provide socialization regarding the preparation of financial statements in accordance with SAK EMKM, so that they already have broad insight when opening a business and are ready to follow further undergraduate studies. This activity is in the form of presentations and questions and answers by lecturers and S1 Accounting students of Universitas Negeri Manado who at that time were conducting Real Work Lectures (KKN) at the location of the school. The benefits obtained by students include previously not knowing about financial accounting standards, after participating in this activity they already know that small businesses must also make financial reports in accordance with standards, which makes it easier to access capital at financial institutions.